2006
DOI: 10.2135/cropsci2005.12-0480
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Maturity Groups, Environments, and Their Interaction Define Mega‐environments for Seed Composition in Argentina

Abstract: Argentina is the largest soybean [Glycine max (L.) Merrill] meal and oil exporter in the world, with crops covering a 23°to 39°S latitude range, allowing the presence of genotypes from different maturity groups (MG). Multi-environment yield trials (MET) for commercial cultivars are conducted each year across the crop area. The aim of this paper was to evaluate the consistency of MG effects and its interaction with environments (E), first to investigate if different mega-environments (ME) for oil, protein, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 13 publications
(26 reference statements)
13
84
2
1
Order By: Relevance
“…(Urano et al, 2007) or on seed oil (Maestri et al, 1998;Bonato et al, 2000;Chung et al, 2003;Fasoula et al, 2004;Albrecht et al, 2008;Bellaloui et al, 2009). On the other hand, the results were lower than the oil content range of 17.2 to 28.5 % reported by Dardanelli et al (2006), since in this last study some of the analyzed cultivars were from soybean maturity groups with higher oil content yield.…”
Section: Resultscontrasting
confidence: 87%
“…(Urano et al, 2007) or on seed oil (Maestri et al, 1998;Bonato et al, 2000;Chung et al, 2003;Fasoula et al, 2004;Albrecht et al, 2008;Bellaloui et al, 2009). On the other hand, the results were lower than the oil content range of 17.2 to 28.5 % reported by Dardanelli et al (2006), since in this last study some of the analyzed cultivars were from soybean maturity groups with higher oil content yield.…”
Section: Resultscontrasting
confidence: 87%
“…The protein content difference among grains classified by 12 × 3/4" and 16 × 3/4" sieves was approximately 2%, which is a significant value for protein meal production for animal feeds. Oil content was not affected by the evaluated experimental factors, thus, it appears that this is a variable that is little affected by environmental conditions (DARDANELLI et al, 2006;GAO et al, 2009;MAEHLER et al, 2003). …”
Section: Resultsmentioning
confidence: 85%
“…The different concentrations of seed constituents among years in both locations reflected the effect of environmental factors on seed composition constituents. It was reported that seed constituents were affected by environment [16,17,40], temperature [17,18], drought [19,21,22,40], and nutrients in soil and seed [3][4][5]. It was reported that seed constituents vary in the same soybean cultivar grown in different years or under different environments in the same year [26].…”
Section: Seed Yield Protein Oil and Fatty Acidsmentioning
confidence: 99%
“…However, seed composition have also shown to be affected by environment [16,17], genotype, maturity, diseases [18][19][20], temperature [17,18] and drought [19,21,22], nutrients in soil and seed [23][24][25], and planting date [26,27]. For example, it was reported that [26] seed composition varied in the same cultivar grown in different years or under different environments in the same year, and seed protein concentration increased as planting was delayed.…”
Section: Introductionmentioning
confidence: 99%